2005
DOI: 10.1016/j.rmed.2004.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of exhaled nitric oxide analysers

Abstract: Currently no published data are available concerning the comparability of different types of NO analysers, making inter-laboratory comparisons difficult. In two sets of experiments we compared 4 and 5 NO analysers, respectively, from 3 different manufacturers using different calibration regimes: calibration with (1) a separate recommended calibration gas for each analyser, (2) a single low concentration for all (394 ppb), and (3) a single high concentration (12.8 ppm). We measured three subjects with known low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 4 publications
0
18
1
2
Order By: Relevance
“…Previous studies comparing NO analyzers demonstrated that FeNO values could differ depending on the device used for the measurements 15,17,18 . Most studies comparing the NIOX MINO with the NIOX showed that FeNO values measured with the NIOX MINO in grass‐pollen allergic adults, 8 asthmatic adults, 10 asthmatic children during birch‐pollen exposure, 7 and heterogeneous subjects 5,11 were somewhat higher than those measured with the NIOX.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing NO analyzers demonstrated that FeNO values could differ depending on the device used for the measurements 15,17,18 . Most studies comparing the NIOX MINO with the NIOX showed that FeNO values measured with the NIOX MINO in grass‐pollen allergic adults, 8 asthmatic adults, 10 asthmatic children during birch‐pollen exposure, 7 and heterogeneous subjects 5,11 were somewhat higher than those measured with the NIOX.…”
Section: Discussionmentioning
confidence: 99%
“…Two analysers from the same manufacturer (desktop and hand‐held device) have been approved for clinical use in the European Union and in the USA (desktop 2003; hand‐held device 2007). There is also evidence that between analyser differences may be important, so care has to be given to quality control issues in relation to both the analyser and reference calibration gas 56,57 …”
Section: Fraction Of No In the Exhaled Breath (Feno)mentioning
confidence: 99%
“…There is also evidence that between analyser differences may be important, so care has to be given to quality control issues in relation to both the analyser and reference calibration gas. 56,57 Chemiluminescence analysers tend to be rather expensive, large and poorly portable, but smaller cheaper portable devices based on an electrochemical cell technique have recently been developed. These demonstrate strong correlations and degree of agreement with the stationary FeNO analyser.…”
Section: Feno Analysersmentioning
confidence: 99%
“…Exhalation against resistance (5-20 cm H 2 O) is the preferred method [6,52]. Thirdly, differences in calibration gases may produce differing results, although analysers from different manufacturers show a sufficient comparability for practical purposes if proper calibration is performed [53]. Fourthly, the influence of ambient NO should be taken into account.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%